2019
DOI: 10.3233/cbm-171177
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of GBP1 predicts poor prognosis and promotes tumor growth in human glioblastoma multiforme

Abstract: This study provides new insights and evidences that high level expression of GBP1 is significantly correlated with progression and prognosis in GBMs. Furthermore, transfection of GBP1 revealed its regulation on migration and invasiveness of glioma cells, decreasing sensitivity of chemotherapeutic agent, shortening survival of tumor-bearing animals. These data demonstrate that GBP1 may serve as a novel prognostic biomarker and a potential therapeutic target for gliomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 32 publications
2
35
0
Order By: Relevance
“…Collectively, our current study supports the notion that GBP1 is a oncoprotein in prostate cancer, and high levels of GBP1 protein expression is significantly associated with aggressive features in cell line models in vitro and associated with malignant features and poor overall survival in clinical samples. This finding is largely in line with a series of cancer studies where oncogenic function of GBP1 is indicated in prostate cancer (25), triple negative breast cancer (23), esophageal squamous cell carcinoma (19), glioblastoma (17,42,43), ovarian cancer (20,24,26,28), lung cancer (21) and oral cancer (18), and higher levels of GBP1 expression have been associated with enhanced tumor cell infiltration, metastasis, therapeutic resistance and shorter survival in these studies (18,20,21,23,25,27,42).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Collectively, our current study supports the notion that GBP1 is a oncoprotein in prostate cancer, and high levels of GBP1 protein expression is significantly associated with aggressive features in cell line models in vitro and associated with malignant features and poor overall survival in clinical samples. This finding is largely in line with a series of cancer studies where oncogenic function of GBP1 is indicated in prostate cancer (25), triple negative breast cancer (23), esophageal squamous cell carcinoma (19), glioblastoma (17,42,43), ovarian cancer (20,24,26,28), lung cancer (21) and oral cancer (18), and higher levels of GBP1 expression have been associated with enhanced tumor cell infiltration, metastasis, therapeutic resistance and shorter survival in these studies (18,20,21,23,25,27,42).…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies on antiviral effects have shown that human GBP1 acts against various RNA viruses such as vesicular stomatitis virus, encephalomyocarditis virus, influenza A virus, classical swine fever virus, and hepatitis C virus (12)(13)(14)(15)(16). Furthermore, GBP1 overexpression is associated with malignant features in different tumor types, such as glioblastoma (17), oral cancer (18), esophageal squamous cell cancer (19), ovarian cancer (20) and lung cancer (21). Increasing evidence indicates an important role of GBP1 in cancer cell growth, invasion/migration and metastasis (21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…The immune and tumor related nature of these three genes are supported by the following published data: (i) IFI30 suppresses mouse primary T cell reactivity in vitro and mouse autoimmunity through cellular redox chemistry and ERK1/2 phosphorylation in vivo, promotes cell proliferation of a glioma cell line, but IFI30 RNA has been associated, with better patient survival rate in breast cancer and diffuse large B cell lymphoma (DLBCL) (9-14), (ii) GBP1 suppresses TCR signaling through lymphocyte cell-specific protein-tyrosine kinase and IL2 production in a human T cell line promotes cell proliferation/anti-apoptosis of a glioblastoma and two breast cancer cell lines, but inhibits cell proliferation of a colon cancer line. Furthermore, GBP1 reduces radioresistance of two human oral and liver cancer cell lines and correlates with better prognosis in melanoma but with poorer prognosis in human glioblastoma (15)(16)(17)(18)(19)(20)(21), (iii) GBP4 inhibits innate responses to viral infection (22) but lacks known tumor related functions to date. Thus, both knock-down and overexpression of these three genes should be tested in the future experiments to define the exact roles of these proteins within specific contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the ICP co-expression network, we searched for potential ICP related genes (ICPRGs) in IFNγ positive tumors that may function as novel ICPs and consequently identified IFI30, GBP1 and GBP4. Based on the identified literature (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22), IFI30, GBP1, and GBP4 suppress mouse primary T cell activation in vitro and mouse innate immune response in vivo while IFI30 and GBP1 appear to increase cell proliferation in a glioma cell line and two breast cancer cell lines but diminish cell proliferation in a colon cancer cell line. Intriguingly, however, IFI30 RNA expression is associated with better patient survival in breast cancer (12) and diffuse large B cell lymphomas (DLBCL) (14) while GPB1 RNA is associated with better patient survival in melanoma (20) but poorer prognosis in human glioblastoma (21).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, several lines of evidence showed that GBP1 correlated with oncogenic process and highly dependent on their context, as its upregulation was linked with better prognosis in some cancer types, such as breast and colorectal cancer [13][14][15] , but associated with radioresistance and chemotherapy resistance, metastasis, and progress in different types of cancer, such as glioblastoma, ovarian cancer, prostate cancer, and breast cancer [16][17][18][19] . Yet, the function and mechanism of GBP1 in GC progression and tumor immune environment remains unknown, which is needed additional investigation urgently.…”
mentioning
confidence: 99%